Acute Effects of Low- and High-Speed Resistance Exercise on Cognitive Function in Frail Older Nursing-Home Residents: A Randomized Crossover Study. (3rd August 2021) - Coelho-Júnior, Hélio J.; Aguiar, Samuel da Silva; Calvani, Riccardo; Picca, Anna; Carvalho, Denise de Azevedo; Zwarg-Sá, Juliana da Costa; Audiffren, Michel; Marzetti, Emanuele; Uchida, Marco Carlos
Abstract : Aim . The present study investigated the acute effects of low- and high-speed resistance exercise on the cognitive function of frail older women living in nursing home. Materials and Methods . Ten institutionalized frail older women were recruited. Rey Auditory Verbal Learning Test and Stroop test were performed before, immediately after, 1 h after, and 24 h after the end of the experimental session. Participants randomly performed low- and high-speed resistance exercise and a control session. Exercise sessions were composed of 4 resistance exercises with 4–8 sets of 4–10 repetitions at moderate intensity. Results . Results indicated that the performance of Rey Auditory Verbal Learning Test was similarly increased immediately after both low- and high-speed resistance exercises. However, only improvements elicited by low-speed resistance exercise remained significant 1 h after the end of the exercise session. No acute effects of resistance exercise were observed on Stroop performance. Conclusion . Our findings indicated that both low- and high-speed resistance exercises acutely increased episodic memory in frail older women, whereas no changes on Stroop were observed.